Enquiry analysis and user opinion of the Drugs in Breastmilk Helpline: a prospective study - Rutter Paul M; Jones Wendy (BMC, 2012)
Abstract Background Since breastfeeding is universally recognised as the ideal way to feed infants, it is understandable, and at times inevitable, that breastfeeding mothers will want, or be required, to take medication. To meet the information demands of breastfeeding mothers and healthcare professionals, a UK charity, The Breastfeeding Network, established a free telephone helpline to answer queries on medicines in breastmilk. This study reports on the enquiries received by the Drugs in Breastmilk Helpline and user opinion of the service. Methods All enquirers to the Helpline between December 2010 and January 2011 were asked if they could be contacted in 2 to 4 weeks to provide more information on their experience of using the service. A combination of telephone semi-structured interviews and email surveys were used depending on whether the enquiry originated via telephone or email. Results Information was gained from 101 participants; 77 women and 24 healthcare professionals. Women reported high levels of service satisfaction (94%, n = 72/77) and healthcare professionals found the information provided useful (92%, n = 22/24). Women used the service for reassurance or because they had received conflicting information or distrusted healthcare professional advice. Healthcare professionals often could not answer questions or took a cautious approach to recommendation (i.e. advised avoidance of medicines whilst breastfeeding); this was often at odds to advice given by staff from the Helpline. Healthcare professionals did not routinely access resources to answer questions, but when they did, showed a lack of confidence in data interpretation. Conclusions The Breastfeeding Networks' Drugs in Breastmilk Helpline provides an important service to breastfeeding women and healthcare staff to make informed decisions on medicine taking whilst breastfeeding. Healthcare professional uncertainty and incorrect advice given to breastfeeding women suggests that healthcare professional education needs improving and that greater use of specialist services should be encouraged.